Advances in the application of platelet-rich plasma in peripheral nerve injuries - Xiao-Yu Dou; Min An (Anesthesiology and Perioperative Science)
Abstract Peripheral nerve injury (PNI) can occur after various types of trauma; these are common clinical injuries. These injuries often result in chronic conditions such as neuropathic pain and permanent disabilities, severely affecting quality of life and work. Achieving optimal repair of injured peripheral nerves remains a focal point of clinical research. In recent years, platelet-rich plasma (PRP) has been increasingly applied in clinical settings due to associated high concentration of various growth factors that promote tissue repair. Here we review advances in PNI repair and the prospect of using autologous PRP as a treatment paradigm.